How gender is associated with physical bullying and victimization across adolescent stages - Ruining Jin; Sunqiuyu Zhang; Fengshi Ren; Xiao Wang; Tam-Tri Le (PLoS ONE, 2026)
Background Physical bullying remains a significant form of peer aggression during adolescence, a developmental period marked by rapid bodily, psychological, and social change. Although gender differences in bullying have been widely documented, less is known about whether the association between gender and physical bullying perpetration and physical victimization varies across adolescent stages in contemporary non-WEIRD settings. Methods This study conducted a secondary data analysis of openly available survey data from 169 school-going adolescents in India. Participants were grouped into three developmental stages: early adolescence (10–12 years, 35.5%), middle adolescence (13–15 years, 49.1%), and late adolescence (16–18 years, 14.8%). Two Bayesian regression models aided by Markov Chain Monte Carlo estimation were used to examine the association between gender and physical bullying perpetration and victimization, and to assess whether age moderated these associations. Findings Male adolescents showed higher levels of both physical bullying perpetration and physical victimization than female adolescents. The association between male gender and physical bullying perpetration became more pronounced across later adolescent stages. By contrast, age did not clearly moderate the association between gender and physical victimization. Implications The findings suggest that bullying prevention in school settings should pay closer attention to gendered peer dynamics, developmental stage, and school climate. In particular, school-wide and developmentally sensitive approaches may be more useful than isolated incident-based responses for addressing physical bullying in adolescent populations.